(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This article provides a concise summary of the main themes and arguments presented in the article "The Global Phenomenon: How Globalization Facilitates the Spread of English." It outlines the interconnected relationship between globalization and the global spread of English, highlighting key factors such as economic integration, cultural hegemony, and technological advancements. The annotation underscores the significance of English as a dominant global language and its implications for cross-cultural communication and linguistic diversity in an increasingly interconnected world.